2018
DOI: 10.1038/s41598-018-32644-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct IR Absorption Spectra of Propargyl Cation Isolated in Solid Argon

Abstract: The direct infrared (IR) absorption spectra of propargyl cations were recorded. These cations were generated via the electron bombardment of a propyne/Ar matrix sample during matrix deposition. Secondary photolysis with selected ultraviolet (UV) light was used for grouping the observed bands of various products. The band assignment of the propargyl cation in solid Ar was performed according by referring to the previous infrared photodissociation (IRPD) and velocity-map imaging photoelectron (VMI-PE) data, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…They show similar behavior upon photolysis at 365 and 160 nm (Figure S2) and may be attributed to the same carrier. Based on our previous studies on electron bombardment of matrix samples at low energy, the observed primary products include ionic precursors and/or fragments missing a hydrogen atom. Therefore, we expect the carrier of these unknown lines to have a backbone similar to that of acetone. We calculated the vibrational wavenumbers of the neutral and ionic forms of possible species and summarized the results in Tables S1–S7.…”
Section: Resultsmentioning
confidence: 99%
“…They show similar behavior upon photolysis at 365 and 160 nm (Figure S2) and may be attributed to the same carrier. Based on our previous studies on electron bombardment of matrix samples at low energy, the observed primary products include ionic precursors and/or fragments missing a hydrogen atom. Therefore, we expect the carrier of these unknown lines to have a backbone similar to that of acetone. We calculated the vibrational wavenumbers of the neutral and ionic forms of possible species and summarized the results in Tables S1–S7.…”
Section: Resultsmentioning
confidence: 99%